2017
DOI: 10.3329/bmrcb.v42i2.32052
|View full text |Cite
|
Sign up to set email alerts
|

Rubella Antibody Prevalence and Immunogenicity of Single Dose Rubella Vaccine Among 16 – 25 Years Girls from Bangladesh

Abstract: Rubella virus infection during pregnancy is an important cause of blindness, deafness, congenital heart disease, and mental retardation of the foetus. Multiple sero-surveys of rubella antibody among reproductive aged females of Bangladesh showed that 20-30% of them remain susceptible to rubella as rubella vaccination is yet not included in our national immunization program for adolescent and adult girls. The present study was designed to conduct a sero-survey among unmarried girls of 16 to 25 years to assess t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…56 This finding is different from that in a study done among childbearing-aged women in Turkey showing 3.8%, 57 4.3% average seronegativity in 17 countries, 49 8.7% in Taiwan, 58 9.1% in Jordan, 59 9.7% in Egypt, 60 15.8% in Singapore, 61 22.9% in eleven Asian countries, 62 and 31.1% in Bangladesh . 63 The pooled prevalence of anti-RV IgM among pregnant women in sub-Saharan African was 5.1%. This finding showed that pregnant women commonly had acute RV infection in sub-Saharan Africa.…”
Section: Discussionmentioning
confidence: 96%
“…56 This finding is different from that in a study done among childbearing-aged women in Turkey showing 3.8%, 57 4.3% average seronegativity in 17 countries, 49 8.7% in Taiwan, 58 9.1% in Jordan, 59 9.7% in Egypt, 60 15.8% in Singapore, 61 22.9% in eleven Asian countries, 62 and 31.1% in Bangladesh . 63 The pooled prevalence of anti-RV IgM among pregnant women in sub-Saharan African was 5.1%. This finding showed that pregnant women commonly had acute RV infection in sub-Saharan Africa.…”
Section: Discussionmentioning
confidence: 96%
“…Pregnant women with overt hypothyroidism are at risk of adverse pregnancy outcomes such as spontaneous abortion, preeclampsia, preterm birth, placental abruption, postpartum hemorrhage, low birth weight, fetal or neonatal hyperthyroidism, neuro-cognitive development disorder of the fetus, intrauterine growth restriction, low IQ of children, increased bilirubin in newborns and increased perinatal mortality [4][5][6][7][8]. Additionally, hypothyroidism of the mother, especially in the rst trimester, is associated with a delay in the child's neural development [1], and the fetuses of hypothyroid women are 10-20% more likely to suffer from congenital abnormalities [4]. In addition, the possibility of having a child with chromosomal disorders and congenital abnormalities exists for every pregnant woman, even without any positive medical history.…”
Section: Introductionmentioning
confidence: 99%
“…9 Girls and women who are currently of reproductive age (15–49 years) and at risk were not included in the programme. 10 The serological status with respect to rubella antibodies is rarely assessed during pregnancy, and serial screening is not advised in these countries. Additionally, screening for hearing defects in neonates is not routinely performed, further delaying the diagnosis of CRS.…”
Section: Introductionmentioning
confidence: 99%